Analisis Kurikulum di Kelompok Bermain Teratai Palembang - Lidia Oktamarina; Diyah Ayu Permata; Ayu Rizkia; Galuh Istiqomah; Vera Juwita; Kireyna Shelomita (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research was motivated by the uniqueness of the curriculum and learning at KB Teratai. To analyze the curriculum in the play group, the aim of this research was to determine the curriculum concept of the educational curriculum development model at KB Teratai, learning implementation strategies, educational calendar and evaluation techniques. This type of research uses qualitative descriptive methods. Data collection techniques were carried out by examining the results of observations, interviews and documentation. In implementing teaching and learning activities at KB Teratai, the K13 curriculum is used which is integrated with Islamic religious education. The curriculum implementation program, namely, learning planning. The first is, the preparation of learning programs, consisting of the preparation of semester programs, weekly activity programs and daily activity programs. The second, namely, teaching and learning activities, consists of; opening activities, core activities and closing activities. The aim of the curriculum and learning at KB Teratai is to help children reach the stages of their development, so it needs to be planned so that the goals can be achieved effectively and efficiently. implementation of observations, carried out periodically and on a scheduled basis.